ANALISIS TASK PERFORMANCE DALAM LINGKUNGAN KERJA: STUDI PERBANDINGAN KARYAWAN GENERASI Z DAN MILENIAL PADA PT. BANK PERKREDITAN RAKYAT SARIKUSUMA SUYA - Achira, Naswa Arindya; Sukoco, Iwan; Sitio, Nurul Mardhiah (POLITEKNIK LP3I JAKARTA, 2026)
Current changes in workforce composition indicate that Generation Z and Millennials dominate the workforce, including in the banking industry, such as PT. Bank Perkreditan Rakyat Sarikusuma Suya (BPR SKS). The differences in characteristics between these generations raise questions about the task performance demonstrated by these two generations. This study aimed to analyze the task performance achievements of Generation Z and Millennial employees in the same workplace in depth, focusing on job quality, job quantity, and job time limits. The research employed a quantitative approach, with questionnaires distributed to employees at BPR SKS as the data collection instrument. Hypothesis testing using an Independent Sample t-test showed a significance value of 0.284, indicating no significant difference between Generation Z and Millennial employees in task performance achievement in the workplace. However, differences in work patterns and perceptions were found between employees from both generations. The study concluded that although there were no significant differences in performance, differences in work patterns and perceptions are important as a basis for a company's Human Resources (HR) management.